2003
DOI: 10.1016/s1074-7613(03)00262-0
|View full text |Cite
|
Sign up to set email alerts
|

The Sμ Tandem Repeat Region Is Critical for Ig Isotype Switching in the Absence of Msh2

Abstract: Deficiencies of the Msh2 protein or the Smu tandem repeat (SmuTR) sequences each reduce isotype switching in mice by about 2- to 3-fold. We find that switching in mice deficient for both Msh2 and SmuTR is nearly ablated. We propose that the SmuTR provides closely spaced cleavage sites that can undergo switch recombination independent of Msh2, whereas cleavages in sequences flanking the SmuTR require Msh2 processing to allow recombinational joining. We also find that changes in Smu sequences alter the focus of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

8
66
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 58 publications
(74 citation statements)
references
References 51 publications
(4 reference statements)
8
66
0
Order By: Relevance
“…In fact, the level of residual switching observed in APE1-deficient cells in this study is remarkably similar to that observed in cells deficient in UNG2. MMR has been shown to be particularly important when core switch repeats were deleted and overlapping AID hot spots were scarce (10,32,33). Among the MMR factors, the MutL␣ (MLH1/ PMS2) complex has been reported to possess a latent endonuclease activity that is activated upon mismatch recognition (34).…”
Section: Discussionmentioning
confidence: 99%
“…In fact, the level of residual switching observed in APE1-deficient cells in this study is remarkably similar to that observed in cells deficient in UNG2. MMR has been shown to be particularly important when core switch repeats were deleted and overlapping AID hot spots were scarce (10,32,33). Among the MMR factors, the MutL␣ (MLH1/ PMS2) complex has been reported to possess a latent endonuclease activity that is activated upon mismatch recognition (34).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, SSBs in opposite strands resulting from deamination of two relatively distant dC need processing by the MMR pathway to be converted into DSBs, which might only then trigger the accumulation of gH2AX and 53BP1 at the damage site (44,45,52). Accordingly, MMR is particularly important to allow CSR using the pre-Sm when the Sm tandem repeats are deleted (53), because the lower AID hot spot frequency in the pre-Sm will most preferentially accommodate staggered breaks. The proposed model for processing SSBs by MMR during CSR predicts that the U:G mismatch is recognized by the MSH2/MSH6 complex.…”
Section: Discussionmentioning
confidence: 99%
“…3), some level of residual CSR occurs upstream and downstream of the position of the deletion boundary (20,21), and the ones occurring upstream in the core S deletion mice would be particularly difficult to explain if R-loops initiated only in the core S region. Because we now know that the R-loops can begin upstream, the breakpoints upstream of the core S in the deletion mice can now be more easily understood.…”
Section: Discussionmentioning
confidence: 99%